1997
DOI: 10.1097/00007890-199701270-00025
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Murine Cardiac Grafts1,2,3

Abstract: Apoptosis, or the induction of programmed cell death, is a mechanism commonly used by cytotoxic T cells to cause target cell lysis. We evaluated the frequency and distribution of apoptotic cells in DBA/2-->DBA/2 heterotopic cardiac isografts, acutely rejecting DBA/2-->C57BL/6 cardiac allografts, and accepted, 60 day DBA/2-->C57BL/6 allografts from mice treated with anti-CD4 Mab (GK1.5) or gallium nitrate (GN). Apoptosis was identified in histologic sections via TUNEL analysis of nuclear DNA fragmentation. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In murine heart allografts, there was prominent apoptosis of cells in the perivascular infiltrates of recipients that had been treated to prevent acute rejection with anti-CD4 antibody. 68 Similarly, in a model of mouse cardiac allograft tolerance induced with antibody to CD40 ligand plus donor immature dendritic cells, there was increased apoptosis of infiltrating leukocytes and T cells in the recipient lymphoid tissues. 66 Induction of tolerance to murine skin grafts with a combination of antibody to CD40 ligand, CTLA4Ig, and rapamycin was associated with marked increase of apoptosis of alloreactive T cells.…”
Section: Leukocyte Apoptosis Is Associated With Spontaneous Tolerancementioning
confidence: 98%
“…In murine heart allografts, there was prominent apoptosis of cells in the perivascular infiltrates of recipients that had been treated to prevent acute rejection with anti-CD4 antibody. 68 Similarly, in a model of mouse cardiac allograft tolerance induced with antibody to CD40 ligand plus donor immature dendritic cells, there was increased apoptosis of infiltrating leukocytes and T cells in the recipient lymphoid tissues. 66 Induction of tolerance to murine skin grafts with a combination of antibody to CD40 ligand, CTLA4Ig, and rapamycin was associated with marked increase of apoptosis of alloreactive T cells.…”
Section: Leukocyte Apoptosis Is Associated With Spontaneous Tolerancementioning
confidence: 98%
“…Apoptosis has also been shown to occur after kidney, liver and heart transplantation (5)(6)(7). Despite important recent findings, the mechanism of cardiomyocyte apoptosis associated with acute cardiac graft rejection remains unclear (8)(9)(10). The involvement of mitochondria in apoptosis has gained increasing interest due to the demonstration that mitochondria can exert a pro-apoptotic effect in in vitro models, and because of the localization of proteins of the Bcl-2 family on the outer membrane of this organelle (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Cells undergoing apoptosis can be distinguished from those undergoing necrosis by several characteristic features, including blebbing of the cell membrane, a reduction in cell volume, and condensation of nuclear chromatin. In animal studies, there is compelling evidence of myocardial apoptosis 1–3 . Some studies have reported myocardial apoptosis in cardiomyopathies or in acute myocardial infarctions in humans 4 .…”
mentioning
confidence: 99%